Intervensi melalui Psikoedukasi untuk Meningkatkan School Well-Being Siswa Kecamatan Ngaliyan: Intervention through Psychoeducation to Improve School Well Being of Ngaliyan District Students - Wihartati, Wening; Sari, Novita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
School well-being influences building a good atmosphere in the educational process in the school environment. This community service strives to ensure students achieve good school well-being. This community service uses qualitative methods with structured written and verbal interviews, and psychoeducation is also provided to students. Community Service by providing psychoeducation for students in Ngaliyan District. Namely, students are given material related to improving school well-being with psychoeducation consisting of relaxation, self-efficacy, and assertiveness. The results of this service showed an increase in school well-being in this community service with psychoeducation, which improved the welfare of elementary school students after being given psychoeducation, compared to before being given psychoeducation.